DEVELOPMENT OF A SELF-DIRECTED PROFESSIONAL LEARNING SCALE HUMAN CAPITAL-ORIENTED FOR VOCATIONAL HIGH SCHOOL TEACHERS IN BUSSINES AND MANAGEMENT SUBJECTS - Ranu, Meylia Elizabeth; Kamdi, Waras; Hadi, Syamsul; Yoto, Yoto (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
The objective of this study was to construct a measurement tool for evaluating self-directed professional learning (SDPL) among teachers in Vocational High Schools within the framework of human capital. The research was carried out using a sample size of 307 teachers who were instructing business management  productive subjects at several vocational high schools located in the province of East Java, Indonesia. The novelty of this research is the development and validation of an instrument called the SPDL instrument to assess the SDPL abilities of vocational teachers. In addition, in order to assess the reliability and validity of a construct measured using a reflective scale, it is necessary to examine the Cronbach Alpha coefficient and the Average Variance Extracted (AVE). All indicators ideally above a threshold of 0.8. Based on the available evidence, it can be inferred that the aforementioned 34 items possess the necessary qualities of validity and reliability, rendering them suitable for utilization as an SDPL scale.